CREATING LOW-COST ANIMATION VIDEO USING ONLINE PLATFORM: A LEARNING MEDIA USER REVIEW - Noviarina Kurniawati (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2020)
Background: A shift in modern learner learning preference and expansive growth of computer capacities leads to a more widely use of multimedia instructions, including animation videos. Creating animation instructions can be time and resource-consuming. A means of low-cost animation video making platform is favorable. This article aims to review an example of online platform for animation video making.Learning Media Review: Powtoonâ is an online video making and editing platform for producing 2D animation videos. It provides animation attributes, i.e. icons, characters, text, background pictures, etc., and editing technology. The features can be accessed in several bundling and pricing alternatives depends on users need. The article also describes some points in terms of advantages and disadvantages of this online platform. Animation in education can be used for gaining learners’ attention; demonstration of a process or procedures; and supporting explanation for conceptual understanding. Brief discussions about educational theories related to animation video development and use are included.Conclusion: Alternatives of online platforms are available and can be used to develop low-cost educational animation video. Teachers as designer should develop a meaningful concept and storyline guided by the application of sound educational theories during the development and in class implementation.